An improved underivatized, cost-effective, validated method for six short-chain fatty organic acids by high-performance liquid chromatography - Esther A. Olonimoyo; Naresh Kumar Amradi; Stephanie Lansing; Akua A. Asa-Awuku; Candice M. Duncan (Journal of Chromatography Open)
A fast analytical method for a High-Performance Liquid Chromatograph coupled with a Photodiode Array detector (HPLC-PDA) for quantifying six short-chain fatty acids: formic, acetic, propionic, butyric, isovaleric, and valeric acids is optimized and validated. The improved method is compared to existing literature, does not require derivatization, and produces rapid results with relatively low chromatographic cost. Elution modes, mobile phase, pH, and column temperature are optimized to improve peak separation and shorten analysis time without derivatization. The optimized method is characterized by a gradient elution mode with flow rates ranging from 1 to 2.5 mL min −1 and a short analysis time (7.6 mins). The limits of detection for all six acids (LOD) ranged from 0.0003 to 0.068 mM, while the limits of quantification (LOQ) ranged from 0.001 to 0.226 mM. The improved method showed acceptable sensitivity, precision, and dynamic range. Validation and quantification were tested using fermentation broth samples. This optimized method is characterized by lower detection limits and a 50 % shorter analysis time and is applicable to aqueous samples with complex matrices.